Den vetenskapliga underrättelseoperationen - Om inhämtning och genus - Petterson, Tobbe (2012)
In this thesis tactical intelligence collection is studied. The aim is to investigate how the intelligence collection is affected by using a gender perspective. In the study interviews with experienced collectors are made and the data is analyzed using content analysis. It is found that gender affects which type of intelligence can be collected and how the collector can act in a tactical situation. There are however constraints, mostly due to organizational behaviour in the collecting organization, that have to be taken into consideration to reach optimal effect in a collection operation. The findings of the study therefore are presented as a generic model of how an intelligence operation with a gender perspective has to be made.
Felaktigt ISBN: 978-91-7473-416-4
Keywords: gender; collection; intelligence; Swedish Armed Forces; Afghanistan